Use of Dexmedetomidine for Magnetic Resonance Imaging under Sedation in a Pediatric Patient with Phenylketonuria - Pallavi, Kumari; Mishra, Rajeeb K.; Goyal, Amit; Ramesh, Venkatapura J.; Patwardhan, Prathamesh M. (Journal of Neuroanaesthesiology and Critical Care, 2020)
Phenylketonuria (PKU) is an inborn error of metabolism caused by a deficiency of the enzyme phenylalanine hydroxylase which results in accumulation of phenylalanine. Patients of PKU presents with seizures, mental retardation, and organ damage and possess a unique challenge to the anesthesiologists when they need anesthetics for diagnostic or surgical procedures. There is limited literature regarding the safety of various anesthetic drugs in PKU patients. None of them reported the use of dexmedetomidine as safer sedative option for such patients. Therefore, we describe the management of such a case posted for magnetic resonance imaging under dexmedetomidine sedation.
Keywords: phenylketonuria; dexmedetomidine; propofol; magnetic resonance imaging; sedation